2017
DOI: 10.1128/aem.02412-16
|View full text |Cite
|
Sign up to set email alerts
|

Influences of pH and Iron Concentration on the Salivary Microbiome in Individual Humans with and without Caries

Abstract: This study aimed to identify the differences in the oral microbial communities in saliva from patients with and without caries by performing sequencing with the Illumina MiSeq platform, as well as to further assess their relationships with environmental factors (salivary pH and iron concentration). Forty-three volunteers were selected, including 21 subjects with and 22 without caries, from one village in Gansu, China. Based on 966,255 trimmed sequences and clustering at the 97% similarity level, 1,303 species-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 53 publications
3
34
0
2
Order By: Relevance
“…On the other hand, a recent study also showed that systemic diseases have significant influence on the oral microbiota [22]. Salivary urate is reported to be significantly increased in gout and higher concentrations may change the oral microenvironment, such as the pH of saliva [13], which has been demonstrated to be an important factor that affects the balance of oral microbial communities [23,24]. In addition to uric acid, there might be many other metabolites that are altered in the saliva of gout/HUA patients that contribute to the modification of the normal oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study also showed that systemic diseases have significant influence on the oral microbiota [22]. Salivary urate is reported to be significantly increased in gout and higher concentrations may change the oral microenvironment, such as the pH of saliva [13], which has been demonstrated to be an important factor that affects the balance of oral microbial communities [23,24]. In addition to uric acid, there might be many other metabolites that are altered in the saliva of gout/HUA patients that contribute to the modification of the normal oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity is one of the most complex and largest microbial habitats that harbors hundreds of different bacteria which play important roles in maintaining oral homeostasis and influencing the development of both oral and systematic diseases [4]. Many factors in the oral environment including intraoral pH and salivary iron concentration as well as expression of serum malondialdehyde and lipid profile have been reported to have significant relationships with oral microbial communities [5,6]. Several recent studies detected the efficacy of antibiotics or drug composed of herbal on oral microbiol communities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The significant influences of the oral environment observed in this study increase the current understanding of the salivary microbiome in caries. These results will be useful for expanding research directions and for improving disease diagnosis, prognosis, and therapy [67].…”
Section: Role Of Diagnostic Propertiesmentioning
confidence: 92%